Comparative genomics analysis of Ganoderma orthologs involved in plant-pathogenesis - Ho, Chai-Ling (Multidisciplinary Digital Publishing Institute, 2023)
Ganoderma species are producers of bioactive secondary metabolites and lignin degraders. A few Ganoderma species are known to be plant pathogens that attack economically important trees. In this study, comparative genomics analysis was conducted on the proteome of ten Ganoderma species/strains, focusing on the proteins that have been reported to be involved in plant-pathogenesis in other fungi. Fungal trophic lifestyle prediction of these Ganoderma species/strains supported that G. boninense (a potent pathogen to oil palm) is a hemibiotrophic fungus while the other Ganoderma species/strains analyzed were predicted to be saprophytes or a symbiont based on their Carbohydrate-Active Enzyme (CAZyme) contents. Although these Ganoderma species/strains were demonstrated to share many CAZymes and secondary metabolite core gene clusters, individual species may produce unique CAZymes and secondary metabolite core genes that determine their lifestyles, host-specificity, and potential as a producer of bioactive secondary metabolites. Ortholog groups that are related to fungal virulence from seven Ganoderma species/strains including those involved in lignin degradation, mycotoxin, siderophore and ergosterol biosynthesis, and virulence were summarized. Potential effectors were predicted from the proteome of these Ganoderma species/strains, and putative effectors that were being expressed in G. boninense in oil palm roots but not found in other species were identified. The findings provide a useful resource to further analyze plant-pathogenesis and wood degradation activities of these Ganoderma species.